Análise da fragilidade ambiental na bacia hidrográfica do Rio das Almas, GO - Vespucci, Ariel Godinho (2020)
The Das Almas River Basin (BHRA) is one of the main affluent from Serra da Mesa reservoir in northern Goiás, covering Central Goiano Mesoregion and part of Northwest, North and East regions in Goiás. There are 38 municipalities served by important infrastructure roads focused on national macroeconomics (Ferrovia Norte-Sul and BR-153), which are fundamental to the occupation history of this region. With growing process of transforming the Cerrado native vegetation into anthropic uses encouraged by public policies for agricultural and industrial development, the pressure on BHRA's natural resources has increased. This study proposes an analysis of BHRA's Environmental Fragility evolution (ROSS, 1994), which fragility degrees result from the interaction and interdependence of components in natural and socioeconomic systems. So, BHRA's environmental fragility evolution was analyzed by comparing the fragility maps of the years 1985, 1995, 2005 and 2018, produced by the cartographic data intersection of physical environment with those of land use and occupation in the corresponding years. The results indicate that biotic and socioeconomic factors dynamics are responsible for different forms of occupation of this region and the evolution of BHRA's environmental fragility, since the morphopedological characteristics do not change in analysis time scale. Throughout the study period, the remaining vegetation is concentrated in higher altitudes regions, with greater relief dissection, while anthropic use occurs in flatter areas, with better soils and less dissection. Over the years studied, the gains in strong and medium fragility areas followed the losses in Cerrado areas and pastures and agriculture gains in the first two decades. This link between Cerrado areas and environmental fragility in BHRA becomes more evident when, from 2005 to 2018, there is a Cerrado recovery (gain of areas) and areas of weak and very weak fragilities, simultaneously the loss pasture and medium fragility areas, accompanied by a drop in growth in strong and very strong fragility areas. The analysis of environmental fragility and the identification of environmental systems are important subsidies for environmental planning aiming sustainable development of the study area.